Pengembangan Karakter dan Keterampilan peserta didik Melalui Kegiatan Ekstrakurikuler - Fitria Kautsari Azizah; Lu’luil Maknun (LPPM Institut Al-Ma`arif Way Kanan Lampung, 2022)
This article aims to describe the results of research on the development of students' character and skills through extracurricular activities. This type of research uses descriptive qualitative methods with a literature study approach. This study emphasizes the ability to analyze and review the literature sources obtained. As a source of data for this research, various scientific journals were searched with Google Scholar for relevant articles. The results of this study indicate that extracurricular activities can be used as an effort to develop students' character and skills. Character development which includes 1) tolerance; 2) discipline; 3) independence; 4) love of peace; 5) care for the environment; 6) social care; 7) responsibility; 8) selfconfidence; and others. As well as skills that include 1) creative; 2) collaboration; 3) communication; 4) critical thinking.